IMPLEMENTASI HYBRID ENCRYPTION DENGAN HMAC PADA SISTEM PENGADUAN MASYARAKAT DI DESA SINGARAJAN KABUPATEN SERANG - Mahbub Ahwani; Ahmad Munawir; Mochammad Darip (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Advances in information technology are driving the digitization of public services, including public complaint handling at the village level. The complaint process in Singarajan Village is still carried out manually, resulting in ineffective documentation, difficulty in monitoring follow-up actions on complaints, and potential risks to data confidentiality and integrity. This study aims to develop a mobile-based public complaint system capable of improving the effectiveness of complaint management while ensuring data security through a combination of the RSA and AES-256-CBC algorithms and HMAC-SHA256 authentication. The research method used is a mixed-methods approach, with the system development phase following the SDLC Waterfall model, including requirement analysis, design, coding, testing, and maintenance. System testing was conducted using Black Box Testing to evaluate the application’s functionality and the System Usability Scale (SUS) to measure usability. The research results show that all major system functions operate as intended; the hybrid encryption process successfully maintains the confidentiality of complaint data, while HMAC is able to verify data integrity during the communication process. The SUS test results yielded an average score of 61.33, which falls into the “Marginal Acceptable” category with a grade of D; thus, the application is deemed usable, although it still requires improvement in terms of ease of use. Keywords: Complaint System; Hybrid Encryption; RSA; AES-256-CBC; HMAC-SHA256; Waterfall SDLC.   Abstrak: Perkembangan teknologi informasi mendorong digitalisasi layanan publik, termasuk pelayanan pengaduan masyarakat di tingkat desa. Proses pengaduan di Desa Singarajan masih dilakukan secara manual sehingga menyebabkan pendokumentasian kurang efektif, tindak lanjut pengaduan sulit dipantau, serta berpotensi menimbulkan risiko terhadap kerahasiaan dan integritas data. Tujuan penelitian ini ialah mengembangkan sistem pengaduan masyarakat berbasis mobile yang mampu meningkatkan efektivitas pengelolaan pengaduan sekaligus menjamin keamanan data menggunakan kombinasi algoritma RSA-2048, AES-256-CBC, dan autentikasi HMAC-SHA256. Metode penelitian yang digunakan adalah Mixed Method dengan tahapan pengembangan sistem SDLC Waterfall, meliputi requirement analysis, design, coding, testing, dan maintenance. Pengujian sistem dilakukan menggunakan Black Box Testing untuk menguji fungsionalitas aplikasi serta System Usability Scale (SUS) untuk mengukur tingkat usability. Hasil penelitian menunjukkan bahwa seluruh fungsi utama sistem berjalan sesuai dengan kebutuhan, proses hybrid encryption berhasil menjaga kerahasiaan data pengaduan, sedangkan HMAC mampu memverifikasi integritas data selama proses komunikasi. Hasil pengujian SUS memperoleh nilai rata-rata 61,33, yang termasuk kategori Marginal Acceptable dengan grade D, sehingga aplikasi dinilai telah dapat digunakan, meskipun masih memerlukan peningkatan pada aspek kemudahan penggunaan. Kata kunci: Sistem Pengaduan; Hybrid Encryption; RSA-2048; AES-256-CBC; HMAC-SHA256; SDLC Waterfall.